Keterancaman Bahasa Roswar: Analisis Daya Hidup Bahasa - Santy Yulianti; Winci Firdaus (Badan Pengembangan dan Pembinaan Bahasa, 2020)
Roswar language is one of the languages in West Papua which has less than 5000 native speakers, so this language vitality study is needed to measure the vitality of the Roswar language. This paper is the result of research on the vitality of the Roswar language in Waprak and Nordiwar Villages, Roswar District, Teluk Wondama Regency, West Papua Province. This study aims to describe the language vitality in Papua/West Papua. The scope of this research is based on sociolinguistic theories, especially those related to the vitality of language and endangered languages. The use of language in the written domain/expression domain, use of language in the religion domain, and the use of language in the education domain are mostly at a level of decline. Language vitality which is at a threatened level is the use of language in the transactions domain. The vitality of Roswar language is based on the P value (P-value) which explains the relationship between the variables in each index compared to the mobility of the informants in the relative urban-rural position, the use of language in the family domain, the use of language in the written expression domain, the use of language to express expression of feelings, use of language in the religion domain, and use of language in the government domain. AbstrakTulisan ini merupakan hasil penelitian vitalitas bahasa Roswar di desa Waprak dan Nordiwar, Distrik Roswar, Kabupaten Teluk Wondama, Provinsi Papua Barat. Penelitian ini bertujuan mendeskripsikan vitalitas bahasa di Papua/Papua Barat. Cakupan penelitian ini didasarkan pada teori-teori sosiolinguistik khususnya yang berkaitan dengan vitalitas bahasa dan bahasa terancam punah. Penggunaan bahasa pada ranah/ekspresi tulis, penggunaan bahasa pada ranah keagamaan, dan penggunaan bahasa pada ranah pendidikan sebagian besar berada pada tingkat mengalami kemunduran. Vitalitas bahasa yang berada pada tingkat terancam adalah penggunaan bahasa pada ranah transaksi. Vitalitas bahasa Roswar berdasarkan nilai P (P-value) yang menerangkan keterkaitan variabel-variabel dalam tiap indeks yang dibandingkan berada di ranah mobilitas informan pada posisi relatif kota-desa, penggunaan bahasa pada ranah keluarga, penggunaan bahasa pada ranah/ekspresi tulis, penggunaan bahasa untuk mengungkapkan ekspresi perasaan, penggunaan bahasa pada ranah keagamaan, dan penggunaan bahasa pada ranah pemerintahan.